Agmatine is transported into liver mitochondria by a specific electrophoretic mechanism - Salvi, Mauro (2006)
Agmatine, a divalent diamine with two positive charges at physiological pH, is transported into the matrix of liver mitochondria by an energy-dependent mechanism the driving force of which is DeltaPsi (electrical membrane potential). Although this process showed strict electrophoretic behaviour, qualitatively similar to that of polyamines, agmatine is most probably transported by a specific uniporter. Shared transport with polyamines by means of their transporter is excluded, as divalent putrescine and cadaverine are ineffective in inhibiting agmatine uptake. Indeed, the use of the electroneutral transporter of basic amino acids can also be discarded as ornithine, arginine and lysine are completely ineffective at inducing the inhibition of agmatine uptake. The involvement of the monoamine transporter or the existence of a leak pathway are also unlikely. Flux-voltage analysis and the determination of activation enthalpy, which is dependent upon the valence of agmatine, are consistent with the hypothesis that the mitochondrial agmatine transporter is a channel or a single-binding centre-gated pore. The transport of agmatine was non-competitively inhibited by propargylamines, in particular clorgilyne, that are known to be inhibitors of MAO (monoamine oxidase). However, agmatine is normally transported in mitoplasts, thus excluding the involvement of MAO in this process. The I2 imidazoline receptor, which binds agmatine to the mitochondrial membrane, can also be excluded as a possible transporter since its inhibitor, idazoxan, was ineffective at inducing the inhibition of agmatine uptake. Scatchard analysis of membrane binding revealed two types of binding site, S1 and S2, both with mono-co-ordination, and exhibiting high-capacity and low-affinity binding for agmatine compared with polyamines. Agmatine transport in liver mitochondria may be of physiological importance as an indirect regulatory system of cytochrome c oxidase activity and as an inducer mechanism of mitochondrial-mediated apoptosis.